Análise comparativa do tecido gengival de ratos em uso dos imunossupressores ciclosporina e tacrolimus - Eugenio Jose Pereira Lages (2001)
The purpose of this experimental study was to evaluate and compare the possible morphological alterations in the gingival tissues of rats, under the administration of the imunossupressors cyclosporine and tacrolimus. This research was motivated by the high prevalence of gingival overgrowth associated with the use of cyclosporine, which can cause aesthetic, phonetic and functional alterations, and also by the reports of clinical cases that had shown significant decrease in gingival overgrowth after the replacement of the cyclosporine by the tacrolimus. The sample included 50 Sprague Dawley male rats, four to six weeks old, with an average weight of 165 to 225 grams. The animals were divided in five groups and received, during 54 days, through oral medication, therapeutic and higher than therapeutic doses in order to exacerbate the possible negative side effects. The animals were homogeneously selected and divided in groups, according to their weight. After animal selection, three groups were established. The Control Group (Cg), with 10 animals, received distilled water. The cyclosporine Group (Cs), made up of 20 animals, was subdivided in two sub groups of ten animals that received 10mg/kg/day (Cs1) and 30mg/kg/day (Cs2) of cyclosporine respectively. The tacrolimus group (Tc), also of 20 animals, was subdivided in two sub groups of ten animals that received 3,2mg/kg/day (Tc1) and 6,4mg/kg/day (Tc2) of tacrolimus respectively. The results have shown that the cyclosporine induced overgrowth in the groups treated with this medication. The severity of this overgrowth was higher in the animal group that received a higher cyclosporine dosage (Cs2) than in the group that received the therapeutic dose, showing a positive relation between dose and severity of gingival overgrowth. Based on this study evidences, we can suggest a possible prescription for the substitution of the cyclosporine by the tacrolimus in the individuals who show severe gingival overgrowth.